Analisis Faktor - Faktor yang Mempengaruhi Online Purchase Intention pada Situs Belanja Online - Renza Fahlevi; Anthony Anthony (Jurnal Mirai Management, 2022)
This study aims to determine and analyze the factors that influence online purchase intention shopping sites online which include performance expectancy, effort expectancy, facilitating conditions, social influence, personal innovativeness, and perceived trust which are moderated by gender. The survey conducted for this research is by distributing questionnaires to 365 respondents. The method used in the selection of this research sample using purposive sampling method, namely by distributing questionnaires to the public with a total of 357 complete and can be processed data. Researchers used the SPSS and Smart PLS programs to analyze the factors that influence online purchase intention shopping sites online. This study shows that the variables of performance expectancy and personal innovativeness have a significant positive effect on the online purchase intention. However, the variables of effort expectancy, facilitating conditions, social influence, perceived trust and independent variables on the dependent variable moderated by gender have no significant effect on the online purchase intention except facilitating conditions. Keywords: Performance expectancy, effort expectancy, facilitating conditions, social influence, personal innovativeness, perceived trust, gender